2022
DOI: 10.1111/1365-2745.13892
|View full text |Cite
|
Sign up to set email alerts
|

Warming may extend tree growing seasons and compensate for reduced carbon uptake during dry periods

Abstract: 1. Warming and drought alter plant phenology, photosynthesis and growth with important consequences for the global carbon cycle and the earth's climate. Yet, few studies have attempted to tease apart their effects on tree phenology, particularly leaf senescence, and on source and sink activity.2. We experimentally assessed the single and combined effects of warming and reduced soil moisture on the phenology (leaf-out and senescence date, growing season length) and above-ground sink (height and diameter growth,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 99 publications
1
18
0
Order By: Relevance
“…( 2021 ), Grossiord et al . ( 2022 )). The OTCs were covered by mobile glass roofs kept closed during the whole experiment to exclude natural precipitation.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…( 2021 ), Grossiord et al . ( 2022 )). The OTCs were covered by mobile glass roofs kept closed during the whole experiment to exclude natural precipitation.…”
Section: Methodsmentioning
confidence: 99%
“…The experimental set-up consisted of 16 hexagonal glass-walled open-top chambers (OTCs) of 3 m height and 6 m 2 area (Fig. 1; Sch€ onbeck et al (2021), Grossiord et al (2022)). The OTCs were covered by mobile glass roofs kept closed during the whole experiment to exclude natural precipitation.…”
Section: Experimental Designmentioning
confidence: 99%
“…The extension of growing season length might have several positive and negative implications for trees. In boreal forests, longer growing seasons are expected to increase forest productivity due to enhanced carbon sequestration (Devi et al., 2020; Grossiord et al., 2022). However, the growing season extension also means more favourable conditions for the proliferation of pests, potentially leading to outbreaks and increased damage to tree populations.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, enhanced springtime ET can lead to reductions in soil moisture which may limit C uptake in late summer and autumn (Buermann et al., 2018; Lian et al., 2020). On the other hand, increased carbon uptake when spring arrives early may dampen the impact of subsequent dry downs on annual C uptake (Grossiord et al., 2022). For example, Roman et al.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, enhanced springtime ET can lead to reductions in soil moisture which may limit C uptake in late summer and autumn (Buermann et al, 2018;Lian et al, 2020). On the other hand, increased carbon uptake when spring arrives early may dampen the impact of subsequent dry downs on annual C uptake (Grossiord et al, 2022). For example, Roman et al (2015) showed that an early start to spring substantially mediated the negative impacts of the extreme 2012 flash drought on fluxes in the long-running Morgan-Monroe State Forest AmeriFlux site.…”
mentioning
confidence: 99%